Estimating the proportion of plasmodium vivax recurrences caused by relapse: A systematic review and meta-analysis - Commons, RJ; Simpson, JA; Watson, J; White, NJ; Price, RN (American Society of Tropical Medicine and Hygiene, 2020)
Plasmodium vivax and Plasmodium ovale form dormant liver hypnozoites that can reactivate weeks to months following initial infection. Malaria recurrences caused by relapses are an important cause of morbidity and source of transmission. To estimate the proportions of P. vivax malaria recurrences caused by relapses in different geographical locations, we systematically reviewed clinical efficacy studies of uncomplicated P. vivax malaria, in which patients were randomized to treatment with or without radical cure primaquine regimens and were followed up for 1 year. The minimum proportion of recurrences caused by relapses was estimated for each study site by assuming primaquine prevented all relapses and did not augment blood-stage efficacy. Of the 261 studies identified, six were eligible enrolling 4,092 patients from 14 treatment arm comparisons across seven countries. Of the 2,735 patients treated with primaquine, 24.3% received low dose (2.5 to < 5.0 mg/kg total) and 75.7% received high-dose primaquine (³ 5.0 mg/kg total). The overall pooled incidence rate ratio of P. vivax relapses for patients treated with primaquine versus no primaquine was 0.15 (95% CI: 0.10–0.21; I 2 = 83.3%), equating to a minimum of 79% of recurrences attributable to relapse. Country-specific incidence rate ratios ranged from 0.05 (95% CI: 0.01–0.34; one estimate) in Pakistan to 0.34 in Nepal (95% CI: 0.12–0.83; one estimate) and Afghanistan (95% CI: 0.22–0.51; three estimates). Relapses account for a very high proportion of recurrent infections following schizontocidal treatment of acute P. vivax malaria across diverse geographic locations. This emphasizes the importance of implementing hypnozoitocidal treatment.